2022
DOI: 10.3389/fchem.2021.819165
|View full text |Cite
|
Sign up to set email alerts
|

Targeting SARS-CoV-2 Proteases for COVID-19 Antiviral Development

Abstract: The emergence of severe acute respiratory syndrome (SARS-CoV-2) in 2019 marked the third occurrence of a highly pathogenic coronavirus in the human population since 2003. As the death toll surpasses 5 million globally and economic losses continue, designing drugs that could curtail infection and disease progression is critical. In the US, three highly effective Food and Drug Administration (FDA)–authorized vaccines are currently available, and Remdesivir is approved for the treatment of hospitalized patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 136 publications
1
88
0
Order By: Relevance
“…Multiple small-molecule inhibitors of M pro have been described, including GC376 and boceprevir, with in vitro 50% inhibitory concentration (IC 50 ) values of 0.03 to 0.19 μM and 1.6 to 8.0 μM, respectively ( 8 , 27 , 28 ). GC376 was developed against a panel of 3C and 3C-like cysteine proteases ( 29 , 30 ), and boceprevir was developed as an inhibitor of the NS3 protease of hepatitis C virus ( 1 , 31 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple small-molecule inhibitors of M pro have been described, including GC376 and boceprevir, with in vitro 50% inhibitory concentration (IC 50 ) values of 0.03 to 0.19 μM and 1.6 to 8.0 μM, respectively ( 8 , 27 , 28 ). GC376 was developed against a panel of 3C and 3C-like cysteine proteases ( 29 , 30 ), and boceprevir was developed as an inhibitor of the NS3 protease of hepatitis C virus ( 1 , 31 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV-2 (SARS2) has two proteases, papain-like protease (PL pro , Nsp3) and main protease/3C-like protease (M pro , 3CL pro , Nsp5), which are responsible for 3 (Nsp1-4) and 11 (Nsp4-16) viral polyprotein cleavage events, respectively ( 4 7 ). These cleavage events are essential for the formation of the viral replicase complex and pathogenesis, and therefore, both of these SARS2 proteases are under intensive investigation for the development of drugs to combat the ongoing COVID-19 pandemic ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, gamma-lactam rings, for example, are frequently substituted for carbonyl groups. Besides, some studies, have attempted to design drugs by adding non-polar and aromatic groups to the compounds in order to reduce the amount of drug-protein binding in the blood and the volume of distribution in the body while also increasing the drug's tropism within the lungs [ 153 ]. It is worth noting that virtual screening of potential Mpro inhibitors has also confirmed that Lewis acid structures such as bortezomib, which contains boron metal bind to M-protein with ease [ 154 ].…”
Section: Discussionmentioning
confidence: 99%
“…Monomeric M pro consists of an N-terminal finger (residues 1-7) and three domains: the chymotrypsin-like domain I (residues 8-101), the picornavirus 3C protease-like domain II (residues 102-184) and domain III (residues 201-306) 42 . Dimerization is needed for M pro function, as interaction between the protomers, in particular the interaction between the Nterminal S1 of one protomer and E166 of the other promoter, keeps the enzyme in an active conformation 37 .…”
Section: Sars-cov-2 M Pro (3cl Pro or Nsp5)mentioning
confidence: 99%
“…However, due to its low oral bioavailability, it has been superseded by the oral drug, PF-07321332 (EUA-approved nirmatrelvir), which does not interact with any residue under positive selection pressure. Interestingly, G15, K90, and P132, which are often mutated in current SARS-CoV-2 variants of concern 42 , are under positive selection. Since the mutation of K90 to Arg is expected to improve dimerization 42 , it may affect compounds that target the dimer interface.…”
Section: Sars-cov-2 M Pro (3cl Pro or Nsp5)mentioning
confidence: 99%